Multimodality imaging leads to increased diagnostic certainty for the endocarditis multidisciplinary team. (4th February 2022) - Brown, LAE; Loganath, K; Mangouretsios, G; Lee, M; Steadman, CD; Carpenter, JP; O"kane, PD
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): NA Background Endocarditis is a complex condition with high rates of morbidity and mortality. The clinical presentation is highly variable and diagnosis may be difficult. ESC guidelines include modified diagnostic criteria utilising both Duke criteria and multimodality imaging techniques in order to improve sensitivity. A Multidisciplinary Endocarditis Team (MDT) is recommended to improve patient care and has been shown to reduce 1 year mortality. We have established a local endocarditis team, with remote input from our regional cardiothoracic centre. During weekly virtual multidisciplinary meetings (MDM), all patients with suspected endocarditis are discussed, with recommendations on investigations, antimicrobial therapy and management. Purpose We audited the use of multimodality imaging in the diagnosis of endocarditis before and after the implementation of the MDM to compare management strategies. Methods Inpatients who were clinically diagnosed and treated for endocarditis in the first 6 months of 2019 (pre MDT – Group 1, n = 30) and 2021 (with MDT input - Group 2, n = 21) were included. Likelihood of endocarditis was calculated using the modified Duke score and multimodality imaging, resulting in categories of definite IE, possible IE and rejected IE. Imaging specifically requested for the diagnosis of endocarditis (or infection/embolic source) was recorded. Where imaging criteria were demonstrated, the modality making this diagnosis was recorded. Results In both groups all patients had a transthoracic echocardiogram (TTE) with a similar diagnostic yield: (20%) in group 1 and 6(29%) in group 2, p = 0.481. In group 1, 13 patients without diagnostic criteria on TTE had a second investigation, with a further 4 meeting imaging criteria. 1 patient had a third test. In group 2, 13 had a second test with a further 8 meeting imaging criteria. 3 patients had a third test with 1 further positive result (Figure 1). There was increased usage of additional testing after a normal TTE in group 2 (87%) compared to group 1 (54%), p = 0.036. Overall, in group 1, 10(33%) patients demonstrated imaging criteria for endocarditis. In group 2, this increased to 15(71%), p = 0.008. A wider spread of imaging techniques was used in group 2 (Figure 1). In group 1, diagnostic criteria were found on TTE (60%) or TOE (40%). In group 2, they were seen from all four modalities: TTE (40%), TOE (33%), FDG-PET (20%) and CT (7%). In group 1, the spread of diagnostic classification was: Definite endocarditis - 6(20%) Possible endocarditis - 13(43%) Rejected endocarditis - 11(37%) In group 2, this was: Definite endocarditis - 12(57%) Possible endocarditis - 9(43%) Conclusion: Creation of endocarditis MDT resulted in increased use of multimodality imaging in patients with suspected endocarditis, resulting in a higher diagnostic yield and an increase in diagnostic certainty.